2021
DOI: 10.1186/s40662-021-00263-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of two first-generation trabecular micro-bypass stents (iStent) with phacoemulsification in primary open-angle glaucoma: eight-year results

Abstract: Background The short- and medium-term outcomes of iStent have been extensively studied; however, only few studies have investigated its long-term outcomes. Here, we assessed the long-term efficacy and safety of two iStents with concomitant cataract surgery in glaucomatous eyes while also evaluating measures of disease stability using visual field and optical coherence tomography (OCT) of the optic nerve and the macula throughout 8 years of follow-up. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…This was a single-arm, open-label trial, consistent with FDA standards for a 510(k) device registration submission. Although the follow-up period of 12 months is of relatively short duration, the iStent infinite has the same mechanism of action and treatment approach as the first-generation iStent and second-generation iStent inject devices, which have shown consistent durability in maintaining IOP and medication reductions for up to 8 years postoperative 16–18,20–32,37–39. Hence, long-term studies with iStent infinite would be expected to demonstrate similarly consistent effectiveness and safety over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was a single-arm, open-label trial, consistent with FDA standards for a 510(k) device registration submission. Although the follow-up period of 12 months is of relatively short duration, the iStent infinite has the same mechanism of action and treatment approach as the first-generation iStent and second-generation iStent inject devices, which have shown consistent durability in maintaining IOP and medication reductions for up to 8 years postoperative 16–18,20–32,37–39. Hence, long-term studies with iStent infinite would be expected to demonstrate similarly consistent effectiveness and safety over time.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Beyond the pivotal trials evaluating combined procedures for mild to moderate primary OAG, multiple additional studies have shown that implantation of iStent and iStent inject can effectively and safely reduce IOP and medication burden in both combined (with phacoemulsification) and stand-alone (without phacoemulsification) surgery. [20][21][22][23][24][25][26][27][28][29][30][31][32] The evidence also demonstrates an incremental increase in IOP-reducing and medication-reducing effect with a higher number of iStents (1 vs. 2 vs. 3) 20,[33][34][35][36][37][38][39] and suggests a specific incremental benefit of 3 over 2 stents. 16 Subconjunctival bleb-associated surgeries, which bypass the eye's natural drainage system and create a filtering bleb (eg, trabeculectomy, tube shunt implantation, XEN Gel Stent implantation, Preserflo), may be considered when greater IOP lowering is required.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is a titanium, L-shaped stent (1.00 mm by 0.33 mm) that is inserted ab interno into the trabecular meshwork to re-establish flow of the aqueous humor into Schlemm's canal. The iStent, whether combined with cataract surgery or as a standalone procedure, is well tolerated and has demonstrated sustained long-term efficacy in reducing IOP and medication burden significantly in OAG [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%